Pengaruh Variasi Produk Dan Citra Merek Terhadap Keputusan Pembelian Ulang Pada Susu Setia Di Tenggarong - Febrian Krismonanda; Iskandar Iskandar (FAKULTAS EKONOMI DAN BISNIS UNIKARTA, 2021)
Abstract: The purpose of this study was to analyze the effect of product variations and brand image simultaneously, to analyze product variations and brand image to partial repurchase decisions, and to determine the independent variables that had the most dominant influence on repurchase decisions at Susu Setia. The analytical tool used in this research is multiple regression analysis. Samples were taken using the Slovin formula as many as 99.61 or 100 people. The results showed that the variable product variation and brand image had a simultaneous and partial effect on repurchase decisions at Susu Setia in Tenggarong. In addition, the Brand Image variable has the most dominant influence as seen from the B coefficient value of the Brand Image which is the largest compared to other variables. Based on the characteristics of respondents in the categories of gender, occupation, and age, it is proven that consumers are dominated by the female gender, millennial age with student status. Thus, the promotions carried out by Susu Loyal to increase repurchase decisions are targeted at this segment. Keywords: Product Variation, Brand Image and Repurchase Decision